Lecturers’ commitment and students’ academic achievement: Viewed from teaching evaluation result - Tengku Shahdan, Tengku Noorainum; A. Ghani, Muhammad Faizal; Elham, Faisol (Canadian Center of Science and Education, 2012)
The purpose of this research is to measure the relevance of the Teaching Evaluation Result (TER) as a tool in evaluating the commitment of the lecturers in delivering the course taught.The TER questionnaires should be evaluated from time to time to ensure the quality, reliability and the applicability of each questions represented the commitment of lecturer.The respondents are foundation students (N=433) together with a total of 4 lecturers teaching the surveyed 7 courses. Students’ academic achievement evaluated from their final exam grades and the students are comprised of 85% Indian, 10% Malay and 5% Chinese.Surprisingly, the finding stated that there are more than 30% of the students who have obtained a grade of A- and better, the TER was < 80%.At the same token10% of the students who have secured a grade of A- and better, the TER was 80%.This indicates that a high TER score does not guarantee that the students will perform well academically even though their lecturers give a full commitment.The mean scores of at least two groups of courses are significantly different at = 0.05 level and the mean score of the grades of at least two groups of lecturers are significantly different at = 0.05 level.Thus, the method of Kolmogorov-Smirnov was used to obtain the existence of normality.The results indicated that all of the variables are generally not normally distributed even at a significant level of = 0.01.Therefore, it was found that 13 out of 17 of TER questionnaires to be significant at = 0.01 and 3 out of 17 TER questionnaires to be significant at = 0.05. However, 1 out of 17 of the questionnaires is not significant.Conclusion, the finding helps the management of the university on the relevance of TER used to measure the lecturer’s commitment.However, due to the limitation and the unavailability of matching each student TER towards each lecturers, therefore, the results presented herein is weakly conclusive.It is recommended that future research to incorporate the matching of students TER be made with the lecturers to obtain reliable and conclusive result.